Acute Exercise-Induced Hypoalgesia and Chronic Training Adaptations in Pain Perception Among Athletes: A Systematic Review, Meta-Analysis, and Meta-Regression - Muhammad Aldi Rivai Ginting; Armansyah Maulana Harahap; Yulia Putri; Herviani Sari (Journal of Society Medicine, 2026)
Introduction: Pain perception is a key determinant of athletic performance and injury rehabilitation. Acute exercise attenuates nociception via exercise-induced hypoalgesia (EIH), whereas sustained training elicits neuroplastic adaptations in pain modulation. Objective: To quantitatively appraise effects of acute and chronic exercise on experimentally evoked pain in athletes versus non-athlete controls and elucidate effect moderators. Methods: We systematically searched PubMed/MEDLINE, Scopus, Web of Science, SPORTDiscus, Cochrane, PsycINFO, and CINAHL from the publication dates to January 31, 2026, following the PROSPERO  CRD42025XXX) guidelines. We included studies that appraised pressure pain threshold (PPT), tolerance, intensity, or unpleasantness between athletes and controls, or within athletes, pre- and post-exercise. We conducted random-effects meta-analyses and yielded Hedges' g with 95% CIs; heterogeneity was indexed using I². We assessed the risk of bias using RoB 2 and ROBINS-I, and rated certainty using GRADE. Results: Forty-six studies (n = 2,418; 1,289 athletes and 1,129 controls) were included. Compared to controls, athletes showed elevated tolerance (g = 0.86, 95% CI: 0.62–1.10), heightened threshold (g = 0.42, 95% CI: 0.21–0.63), and attenuated intensity ratings (g = −0.72, 95% CI: −0.98 to −0.46). Acute exercise elicited moderate hypoalgesia in PPT (g = 0.52; 95% CI: 0.36–0.68). Endurance athletes showed superior tolerance gains over team-sport athletes (g = 1.04 vs. 0.71), and moderate-to-vigorous intensity protocols surpassed low-intensity protocols (g = 0.71 vs. 0.18). Training volume and competitive calibre were robust moderators. Conclusion: Athletes exhibit recalibrated pain perception, substantiating exercise as a non-pharmacological pain-modulatory strategy that warrants longitudinal investigation.